Intelligent Predictive Modeling Using Big Data for Drug Selection in Pharmaceutical Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Pharmaceutical Industries huge amounts of structured, unstructured and semi structured data have been generated. This data is heterogeneous in nature and can be referred to as Big Data. There is a need to manage and analyze this data for taking various decisions regarding drug selection. There are various big data analytical tools and techniques exist with the help of which we can analyze massive amount of data. In this paper we discuss about the various tools and techniques available to analyze the data and selecting the best tool for carting out the predictions regarding right product (drug) selection.